CTU101 Hafazan Interactive Memorization (HIM) / Syaimak Ismail, Muhammad Saiful Islam and Aemy Aziz - Ismail, Syaimak; Ismail, Muhammad Saiful Islam; Aziz, Aemy (Universiti Teknologi MARA, Kedah, 2023)
Hafazan Interactive Memorization (HIM) CTU101 is a product of an interactive memorization application that able to assist students in order to complete their hafazan assessment. Fundamental of Islam course with code CTU101 is a core subject of university that compulsory to be taken by all diploma students at UiTM. In order to achieve a good carry mark, one of the assessments is to memorize 1-20 verses of Surah Yasin for acquiring 20 marks. However, students reach the difficulties to fulfil this assessment due to weak memorization the verses of the surah for several reasons; first, time restriction to complete the task, second, students’ profile not considered as a huffaz. Third, students considered this assessment as an obstacle. Upon on these issues, Hafazan Interactive Memorization (HIM) was introduced to overcome the students’ problem in memorization. Researchers have created an interactive application to test students' memorization and make it easier for them to improve memorization of surah. Based on the survey as tested, the findings indicated students able to achieve high score and managed to memorize with flying colours after using this application. The novelty of this product is i) fun games memorization, ii) enhance a new method of hafazan through HIM, iii) Easy to access and very comprehensive. The benefits of HIM are i) potential tools in monitoring students’ assessment for hafazan ii) Potential tools for assist the lecturer in assessing students’ progress in hafazan assessment, iii) it can be share, apply, adapt, and develop in others organization i.e., university, schools etc. with the same interests.